Value Co-creation in Non-profit Accommodation Platforms - Medina-Hernandez, Vivian C.; Ferrer-Rosell, Berta; Marine-Roig, Estela (Frontiers in Psychology, 2021)
Value co-creation, in the sharing accommodation sector, has been extensively analyzed but mainly with Airbnb as a reference and focusing mostly on guests’ perceptions. The aim of this study is to analyze the value co-created for users (guests and hosts) in the non-profit sharing accommodation platforms Couchsurfing and HomeExchange. This study also aims to analyze whether the co-created value of these platforms differs from that of for-profit platforms, along with how the outcomes, resources, and practices of the value co-creation process can help create wellbeing for individuals involved in the accommodation experience. Given that most of the existing literature on value co-creation in sharing accommodation platforms is based on Airbnb and guest perspectives, this study is a pioneer in analyzing how guests and hosts co-create value in the context of non-profit accommodation platforms using online travel reviews (OTRs) from non-profit platforms, and how the co-created value contributes to the wellbeing of the individuals involved. Results show that a set of tangible and intangible resources, such as the home and its amenities, helps users on non-profit platforms co-create value and that interaction and social practices between guests and hosts help co-create value for both groups. This implies that non-profit accommodation platforms may contribute more to the social dimensions of wellbeing of their users than for-profit platforms such as Airbnb where the host is typically absent from the experience. In addition, this study demonstrates that the co-created value in non-profit platforms depends on the modus operandi of each platform. On Couchsurfing, guests and hosts co-create more value from their social practices, and on HomeExchange, value co-creation depends more on tangible and intangible resources.